Evidence-Based Programming for Older Adults - Marcia G Ory (Frontiers Research Topics, 2015)
There is increased world-wide concern about the impact of multiple chronic conditions, especially among the rapidly aging population. Simultaneously, over the past decade there has been an emergence of state-wide and national initiatives to reduce the burden of chronic conditions that draw upon the translation of evidence-based programs (EPB) into community practice. Yet, little has been written about the national and international implementation, dissemination, and sustainability of such programs. This Research Topic features articles about EBPs for older adults, including a range of articles that focus on the infrastructure needed to widely disseminate EBP as well as individual participant impacts on physical, mental, and social aspects of health and well-being. Using a pragmatic research perspective, this Research Topic will advance knowledge that aims to enhance practice, inform policy and build systems of support and delivery in regard to the reach, effectiveness, adoption, implementation, and maintenance of evidence-based interventions for older adults. The focus is on knowledge transfer rather than knowledge generation but with a dual emphasis on the dissemination and sustainability of EBP that have been tested and shown effective as well as the adaptation of practice-based interventions into evidence-based programs. This Research Topic draws upon grand-scale efforts to deliver these programs, and include both U.S. as well as international examples. Commentaries discuss processes in the development and measurement of EBP and reflect perspectives from program developers and major national and regional funders of EBP as well as professionals and practitioners in the field. The full-length articles focus on four major programmatic areas: (1) chronic disease self-management programs; (2) fall prevention programs; (3) general wellness and physical activity programs; and (4) mental health programs. Additionally, articles are included to discuss cross-cutting issues related to building partnerships and the research infrastructure for the implementation, evaluation, and dissemination of evidence-based programming. The intent of this Research Topic is to enhance practice, inform policy, and build systems of support and delivery for EBP. It is written for a diverse audience and contains practical implications and recommendations for introducing, delivering, and sustaining EBP in a multitude of settings.